Atividade das enzimas β-glicosidase e arilsulfatase em solo arenoso de vinhedo no bioma Pampa - Pawlowski, Estefany (2024)
The activities of soil β-glucosidase and arylsulfatase enzymes have been used to assess soil functioning and to recommend management practices in various types of crops. However, for vineyards, these studies are still incipient. Therefore, this study aimed to evaluate whether the activities of soil β-glucosidase and arylsulfatase enzymes are related to vineyard yield and chemical properties in sandy vineyard soil, and to define the phenological stage of the crop and the soil sampling layer that best characterize these relationships. Soil and plant samples were collected in a commercial vineyard of Vitis vinifera L., located in the extreme south of Brazil, during the 2022/23 season. Soil was sampled at three layers (0-0.05, 0-0.10, and 0-0.20 m) and at four phenological stages (bud burst, full flowering, veraison, and post-harvest). The activity of soil β-glucosidase and arylsulfatase enzymes, nutrient content in soil and leaves, some quality properties of the grape must, and the relative yield of the vineyard (RY) were evaluated. RY is related to the activity of these enzymes, and the best correlations were observed in the post-harvest stage and at a depth of 0-0.10 m. Enzyme activity was also significantly related to soil organic carbon and total nitrogen, as well as other properties, mainly soil nutrients. The activities of β-glucosidase and arylsulfatase enzymes are related to vineyard yield and chemical properties in sandy vineyard soil. For soil sampling, a depth of 0-0.10 m in the post-harvest phenological stage is recommended.